2021
DOI: 10.1590/1414-431x202010162
|View full text |Cite
|
Sign up to set email alerts
|

Is soft drink consumption associated with gestational hypertension? Results from the BRISA cohort

Abstract: It is still unknown whether excessive consumption of sugar-sweetened beverages may be linked to gestational hypertensive disorders, other than preeclampsia. This study investigated the association between soft drink consumption and hypertension during pregnancy, analyzing the relationship from the perspective of counterfactual causal theory. Data from pregnant women of the BRISA cohort were analyzed (1,380 in São Luis and 1,370 in Ribeirão Preto, Brazil). The explanatory variable was the frequency of soft drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…After the removal of duplicates, 4.918 article titles and abstracts were screened. Of these, 151 full-text articles were further assessed for eligibility and, finally, 61 studies [ 4 , 18 , 19 , 20 , 21 , 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the removal of duplicates, 4.918 article titles and abstracts were screened. Of these, 151 full-text articles were further assessed for eligibility and, finally, 61 studies [ 4 , 18 , 19 , 20 , 21 , 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in Africa [ 50 , 51 ], Asia [ 19 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], America [ 4 , 18 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 89 ], Europe [ 20 , 21 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies reported increased obesity, diabetes mellitus, bad oral health, fatty liver, and gout, probably due to increased sugar consumption [11][12][13] . Additionally, sugar-sweetened-beverages (SSBs) consumption has cumulative health hazards and often leads to several health conditions, including malnutrition, obesity, type 2 diabetes, cardiovascular diseases (CVDs), and oral disease [14][15][16] . Thereby, the World Health Organization (WHO), the Scientific Advisory Council on Nutrition, the Dietary Guidelines Advisory Committee 2015, and the American Heart Association, have endorsed substantial limitations on the upper limits of sugar consumption 10,17,18 .…”
mentioning
confidence: 99%